1984
DOI: 10.1073/pnas.81.6.1883
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression of corticotropin-releasing factor and vasopressin immunoreactivity in parvocellular neurosecretory neurons of the adrenalectomized rat.

Abstract: To clarify the anatomical organization that allows for the synergy of vasopressin and oxytocin with corticotropin-releasing factor (CRF) in promoting adrenocorticotropic hormone secretion from the anterior pituitary, immunohistochemical double staining methods were used to compare the distribution of these peptides in the hypothalamic paraventricular nucleus of normal, colchicine-treated, and adrenalectomized male rats. In untreated animals, a few CRFstained cells were found in the parvocellular division of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
198
1
3

Year Published

1990
1990
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 436 publications
(216 citation statements)
references
References 26 publications
12
198
1
3
Order By: Relevance
“…Following ADX, CRH synthesizing parvocellular neurons start to produce AVP (Silverman et al, 1981;Tramu et al, 1983;Kiss et al, 1984;Sawchenko et al, 1984;Davis et al, 1986;Swanson and Simmonds, 1989;Imaki et al, 1991). The change in AVP synthesis was reversible by pretreatment with dexamethasone or corticosterone (Silverman et al, 1981;Davis et al, 1986;Swanson and Simmonds, 1989;Imaki et al, 1991).…”
Section: Peptidesmentioning
confidence: 99%
“…Following ADX, CRH synthesizing parvocellular neurons start to produce AVP (Silverman et al, 1981;Tramu et al, 1983;Kiss et al, 1984;Sawchenko et al, 1984;Davis et al, 1986;Swanson and Simmonds, 1989;Imaki et al, 1991). The change in AVP synthesis was reversible by pretreatment with dexamethasone or corticosterone (Silverman et al, 1981;Davis et al, 1986;Swanson and Simmonds, 1989;Imaki et al, 1991).…”
Section: Peptidesmentioning
confidence: 99%
“…Such pathways may also mediate the effects of AVP. Anatomical studies indicate that CRF-41 neurons, which may also contain AVP (38), lie in close apposition with 8-endorphinergic neurons within the hypothalamus (39). Moreover, AVP, like CRF-41 (11, 12), has been shown to stimulate the release of B-endorphin from hypothalamic tissue in vitro (40) and in vivo (41).…”
Section: Discussionmentioning
confidence: 99%
“…With adrenalectomy, two groups noted that CRHcontaining cells of the PVH, which project to the anterior pituitary via the median eminence, acquired expression of arginine vasopressin (AVP) (9,10). This suggested that CRH and AVP might work together to stimulate the secretion of pituitary ACTH, which was subsequently shown to be correct (11).…”
Section: Regulation Of Crh Secretionmentioning
confidence: 99%